Plant diversity of selected Quercus robur L. and Quercus petraea (Matt.) Liebl. forests in Slovenia - Kutnar, Lado (Zbornik gozdarstva in lesarstva, 2006)
In Slovenia, the plant species diversity on 225 research plots dominated by pedunculate oak (Quercus robur L.) and by sessile oak (Quercus petraea (Matt.) Liebl.) has been analysed. Plots of Q. robur are located in five, andplots of Q. petraea in four semi-natural managed forest complexes. In the tree layer, 28 species were found beside the dominant two oak species, with Carpinus betulus L., Picea abies (L.) Karst., Quercus cerris L. and Fagus sylvatica L. having significant shares of growing stock. Based on the understorey vegetation (shrub and herb layer, terricolous mosses), the Ddetrended Correspondence Analysis (DdCA) made a clear distinction between plots with dominant Q. robur and those with Q. petraea. The understorey vegetation also proved to be a valuable indicator of the site conditions and of forest management in the past. Based on ordination, lowland pedunculate oak forests of relatively long standing near to natural management have been separated from the pedunculate oak forests where spruce was favoured by the forest management, and from the man-made pedunculate oak stands on primary sites of Q. petraea. DCA clearly differentiated the sessile oak forests in warmer climate of Sub-Mediterranean region, and in warmer meso-sites of Pre-Pannonian region from other sessile oak forests. The main gradients of vegetation structure and of species diversity, as well main ecological gradients in different oak forests were obtained by ordination technique.
Keywords: biodiverziteta; lesna zaloga; Quercus petraea; Quercus robur; Slovenia; Slovenija; vegetacija